Role of salt supplementation on vasovagal reactions in young whole blood donors. (10th December 2019) - Kumar, Karan; Sachdev, Suchet; Marwaha, Neelam; Sharma, Ratti Ram
Abstract : Background: The physiologic interventions to prevent vasovagal reactions (VVRs) have been published evaluating water loading, applied muscle tension and salt loading on immediate VVRs (IVVRs), but the effect of salt on delayed VVRs (DVVRs) has not been evaluated. Materials and Methods: Randomized controlled study was conducted enrolling 3060 donors in age group 18–25 years. Control group (CG) donors were given 300 ml of sweetened lime water, with additional 2·5 g salt added in the test group (TG). Results: There were 90 VVRs in 3060 (2·94%, 1 in 34) young college‐going whole blood donors in the present study. This included 57 IVVRs (1·86%, 1 in 54) and 33 DVVRs (1·08%, 1 in 93). There were 53 VVRs (3·49%, 1 in 29) in the CG and 37 VVRs (2·39%, 1 in 57) in the TG, with absolute risk reduction (ARR) of 1·1%. There were 30 IVVRs (1·98%, 1 in 51) in CG and 27 IVVRs (1·74%, 1 in 57) in TG, with ARR of 0·2%%. Significantly, there were 23 DVVRs (1·51%, 1 in 67) in CG and only 10 DVVRs (0·65%, 1 in 154) in the TG, with ARR of 0·9%. One thousand (1000), five hundred (500) and one hundred and eleven (111) young whole donors need to be given 2·5 g of salt supplementation in fluid medium to prevent one VVR, IVVR and DVVR, respectively. The odds and the adjusted odds (AOR) of occurrence of DVVRs were 2·36, 95% CI (1·12–4·98) and 2·40, 95% CI (1·13–5·07) in the CG as against in the TG, on binary and multivariable logistic regression, respectively. Conclusion: There is an overall trend of decrease in VVRs with salt loading in young college‐going whole blood donors, which is statistically evident in the case of DVVRs.